Mesoscale Structure in the Solar Wind - Viall, N. M.; DeForest, C. E.; Kepko, L. (Frontiers in Astronomy and Space Sciences, 2021)
Structures in the solar wind result from two basic mechanisms: structures injected or imposed directly by the Sun, and structures formed through processing en route as the solar wind advects outward and fills the heliosphere. On the largest scales, solar structures directly impose heliospheric structures, such as coronal holes imposing high speed streams of solar wind. Transient solar processes can inject large-scale structure directly into the heliosphere as well, such as coronal mass ejections. At the smallest, kinetic scales, the solar wind plasma continually evolves, converting energy into heat, and all structure at these scales is formed en route. `Mesoscale' structures, with scales at 1 AU in the approximate spatial range of 5 Mm -10,000 Mm and temporal range of 10 s - 7 hrs, lie in the orders of magnitude gap between the two size-scale extremes. Structures of this size regime are created through both mechanisms. Competition between the imposed and injected structures with turbulent and other evolution leads to complex structuring and dynamics. The goal is to understand this interplay and to determine which type of mesoscale structures dominate the solar wind under which conditions. However, the mesoscale regime is also the region of observation space that is grossly under-sampled. The sparse in situ measurements that currently exist are only able to measure individual instances of discrete structures, and are not capable of following their evolution or spatial extent. Remote imaging has captured global and large scale features and their evolution, but does not yet have the sensitivity to measure most mesoscale structures and their evolution. Similarly, simulations cannot model the global system while simultaneously resolving kinetic effects. It is important to understand the source and evolution of solar wind mesoscale structures because they contain information on how the Sun forms the solar wind, and constrains the physics of turbulent processes. Mesoscale structures also comprise the ground state of space weather, continually buffeting planetary magnetospheres. In this paper we describe the current understanding of the formation and evolution mechanisms of mesoscale structures in the solar wind, their characteristics, implications, and future steps for research progress on this topic.